2019
DOI: 10.1002/mp.13368
|View full text |Cite
|
Sign up to set email alerts
|

A fast inverse direct aperture optimization algorithm for intensity‐modulated radiation therapy

Abstract: Purpose The goal of this work was to develop and evaluate a fast inverse direct aperture optimization (FIDAO) algorithm for IMRT treatment planning and plan adaptation. Methods A previously proposed fluence map optimization algorithm called fast inverse dose optimization (FIDO) was extended to optimize the aperture shapes and weights of IMRT beams. FIDO is a very fast fluence map optimization algorithm for IMRT that finds the global minimum using direct matrix inversion without unphysical negative beam weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This economical strategy is not possible with conventional DAO approaches as the objective function value has to effectively be computed before the gradient vector can be calculated. 1 Full details can be found in the original FIDAO paper. 1 The optimization times observed in this study are approaching the reported optimization times of commercial treatment planning systems and by Men et al for GPU-based DAO algorithms for VMAT planning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This economical strategy is not possible with conventional DAO approaches as the objective function value has to effectively be computed before the gradient vector can be calculated. 1 Full details can be found in the original FIDAO paper. 1 The optimization times observed in this study are approaching the reported optimization times of commercial treatment planning systems and by Men et al for GPU-based DAO algorithms for VMAT planning.…”
Section: Discussionmentioning
confidence: 99%
“…1 Full details can be found in the original FIDAO paper. 1 The optimization times observed in this study are approaching the reported optimization times of commercial treatment planning systems and by Men et al for GPU-based DAO algorithms for VMAT planning. 17 standard desktop CPU, without any attempt at parallelization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations